Wpływ regulacji sprężarki upustem powietrza na zapas statecznej pracy - ORKISZ, Marek (Engineering Transactions, 1990)
Przedstawiono analizę wpływu regulacji sprężarki upustem powietrza na zapas stateczności jej pracy oraz ocenę wpływu ilości upuszczanego powietrza na przemieszczenie linii współpracy turbiny i sprężarki w stanach ustalonych. The influence of air-compressor adjustment by means of air-bleed on the reserve of its stable operation Here is presented the analysis of the influence of air-compressor adjustment by means of air-bleed on the stability reserve of its operation and the estimation of the influence of craned away air amount on the shift of turbine and air-compressor cooperation line in stable states.